The Influence of Board of Directors Characteristics, Debt Level, and Firm Size on Financial Performance - Meilani, Revina Putri; Purwaningsih, Eny (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2026)
This study was conducted to analyze the influence of board of directors characteristics, debt levels, and firm size on the financial performance of manufacturing companies in the food and beverage sector. Methodology: The research sample consisted of food and beverage manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the 2022–2024 period, selected using a purposive sampling method. A total of 68 companies met the criteria, resulting in 204 financial statement data points. The criteria included reporting profits consecutively for three years, using Indonesian Rupiah (IDR) as the reporting currency, and having complete financial data relevant to the studied variables. This study performed normality, heteroscedasticity, multicollinearity, and autocorrelation tests. Furthermore, hypothesis testing was conducted using F-tests and t-tests to examine the effects of the independent variables on the dependent variable. Findings: The results of the simultaneous test indicate that the size of the board of directors, the number of female directors, debt level, and firm size simultaneously affect financial performance. Partial testing results show that the size of the board of directors, the number of female directors, debt level, and firm size have a positive effect on financial performance.